Unveiling the Synergy Between the Digital Startup Ecosystem and Entrepreneurship Education: The Role of Digital Personality in Enhancing Students’ Entrepreneurial Intentions - Junianto, Pilifus; Sutrisno, Sutrisno; Syamsuri, Syamsuri; Pramono, Susatyo Adhi; Solihati, Garin Pratiwi; Wanof, M. Indre (LPPM Universitas Pendidikan Mandalika, 2025)
This study examines how the digital startup ecosystem and entrepreneurship education influence university students’ entrepreneurial intentions in Bandung City, with digital personality acting as a mediating variable. A quantitative approach using SEM-PLS was employed, with data collected through an online Likert-scale questionnaire that served as the primary research instrument for measuring perceptions of the digital startup ecosystem, entrepreneurship education, digital personality traits, and entrepreneurial intention. A total of 100 students were selected through purposive sampling, an approach considered sufficient for SEM-PLS analysis, particularly for exploratory models and moderate model complexity. The results show that both the digital startup ecosystem and entrepreneurship education positively influence entrepreneurial intention. However, the digital startup ecosystem exerts its effect only indirectly through digital personality traits such as technological adaptability, digital creativity, and confidence in digital environments. In contrast, entrepreneurship education demonstrates both direct and indirect effects on entrepreneurial intention. The study contributes theoretically by integrating the Theory of Planned Behavior and the Theory of Digital Personality, emphasizing that digital personality acts as a psychological mechanism transforming educational and ecosystem stimuli into entrepreneurial motivation in digital contexts. These findings highlight the importance of incorporating digital personality development into entrepreneurship learning and offer contextual strategies to strengthen youth participation in digital-based entrepreneurship within creative urban ecosystems like Bandung.